A friend mechanism for mobile ad hoc networks - Abd. Razak, Shukor; Samian, Normalia; Maarof, Mohd. Aizaini (IEEE Computer Society, 2008)

(untitled)
In the autonomous environment of mobile ad hoc network (MANET) where nodes are free to move around and depend on each other to initiate communication, cooperation among nodes is an essential component of a successful data transmission process. Since there is no central controller such as router to determine the communication paths in MANET, each node in the ad hoc network has to rely on each other in order to forward packets, thus highly cooperative nodes are required to ensure that the initiated data transmission process does not fail. However, it is hard to encourage cooperativeness among nodes for each node owns limited resources that need to be preserved. These particular nodes which are also known as selfish nodes refuse to help other nodes in forwarding packets due to the anxiety of having resource degradation such as exhausted battery power and limited processor capability. This problem has aroused several issues in MANET: routing, security, Quality of Service (QoS), resource management and auto-configuration. Hence, there is a need to provide a mechanism that can encourage cooperation among nodes without jeopardizing their resources. In this paper, we provide evidence through simulation experiments on how a friendship concept could be used to minimize the number of false alarms raised in MANET Intrusion Detection System (IDS). We also discuss on how the similar friendship concept could be used to address several challenges faced in MANET environment.